IMPLEMENTATION OF LEGAL RESPONSIBILITY OBJECTIONS TO SIMPLE LAWSUITS TO ACHIEVE JUSTICE - Dian Novita; Yenny Eta Widyanti; I Made Sukadana (CV. RADJA PUBLIKA, 2025)
This study examines the implementation of legal remedies for objections in small claims lawsuits at the Manado District Court based on PERMA No. 2 of 2015 in conjunction with PERMA No. 4 of 2019. The problem formulations include: (1) how to apply objections in small claims lawsuits; and (2) what efforts are made to realize justice in this mechanism. The study uses a socio-legal/juridical sociological approach by combining analysis of written legal norms and empirical data through literature studies, decision analysis, and interviews with judges and judicial officials. The results of the study indicate that procedurally and structurally, the objection mechanism at the Manado District Court is basically in accordance with the provisions of PERMA, both regarding procedures and deadlines, so that the principles of simplicity, speed, and low cost are relatively achieved. However, the justice realized is more prominent in the procedural aspect than in the substantive, especially for parties who are not accompanied by legal counsel and have difficulty compiling a legal objection memorandum. The study concludes that the main challenge lies in the legal culture and capacity of the actors, so that it is necessary to increase socialization, legal literacy, legal assistance, and technical guidelines so that objections in small claims are more effective and just.